STUDY HABITS OF THE STUDENTS IN THE UNIVERSITY OF PRISHTINA "HASAN PRISHTINA" - Mrs. Shpresa Dragobuzhda (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Students cannot use the study skills effectively, until they are not having good habits (Bajwa, Gujjar , Shaheen &Ramzan, 2009). This survey report identifies the main study habits of the students of the University of Prishtina (UP), and their impact on students` learning process. 100 undergraduate students of the UP were participants in this study; they were supposed to fill in a questionnaire of 25 questions. This paper outlines the most common study habits of the students of UP. Findings suggested that students posses effective study habits, and that they are aware of the impact that their study habits have in their learning achievement. The results show that students do a study schedule for each semester, and that students feel quite confident with their study habits. However, significant differences are found between the results, and what was expected. Nevertheless, further work is suggested in order to make adjustments in students` learning process.